Accounting, Audit, Analysis: Transformation of Science and Business in New Economic Reality Book of Extended Abstracts - Subačienė, Rasa; Tamulevičienė, Daiva (Vilnius University Proceedings, 2021)
The book includes the abstracts of presentations of fourth international scientific conference “Accounting, Audit, Analysis: Transformation of Science and Business in New Economic Reality” dedicated to the evaluation of the transformation and perspectives of science and business of accounting, audit and analysis in new economic reality.